Mutants of Escherichia coli lacking in highly penicillin-sensitive D-alanine carboxypeptidase activity. - Matsuhashi, M (1977)
Mutants of Escherichia coli lacking in the highly penicillin-sensitive enzyme activities of D-carboxy-peptidase, transpeptidase, and endopeptidase, and with the concomitant absence of penicillin-binding protein 4 of B.G. Spratt and A.B. Pardee [(1975) Nature 254, 516-517] were isolated. The defect of these mutants is ascribed to the lack of an enzyme, D-alanine carboxypeptidase Ib. Genetic mapping studies show the mutation (dacB) to be located at 68 min on the E. coli chromosome map. The dacB mutation results in the simultaneous loss of D-alanine carboxypeptidase and penicillin-binding protein 4. The mutants grew normally under a wide range of growth conditions. We conclude that the enzyme is not a necessary component for normal peptidoglycan biosynthesis in E. coli.